A retrospective analysis of multiparametric ultrasound features in chromophobe renal cell carcinoma - Lin, Xiaoying; Lin, Yucheng; Tang, Lingpeng; Hu, Ting; Wu, Songsong (Frontiers in Oncology, 2025)
ObjectiveTo analyze the echo intensity values, conventional ultrasound features, and contrast-enhanced ultrasound (CEUS) characteristics of chromophobe renal cell carcinoma (chRCC), aiming to provide a valuable reference for the non-invasive clinical diagnosis of chRCC.MethodsThis retrospective study included 52 patients with pathologically proven chRCC at Fujian Provincial Hospital between June 2010 and January 2024, all of whom underwent ultrasound examinations prior to treatment. Two ultrasound specialists assessed the imaging features of each tumor, and 3D Slicer software was utilized to measure the echo intensity values of the renal cortex, renal mass, and renal sinus from the same ultrasound scan plane.Results51.9% of the patients included in this study were male, with an average age of 52.8 years. Quantitative echo intensity measurements showed that only 23.1% (12/52) of the tumors had lower echo intensity compared to the renal cortex, whereas 75.0% (39/52) had values between those of the renal cortex and renal sinus. The median tumor-to-renal cortex echo intensity ratio was 1.18, with the first and third quartiles (Q1, Q3) being 1.01 and 1.78, respectively. Conventional ultrasound analysis revealed that 80.8% (42/52) of the tumors exhibited a regular shape, while 78.9% (41/52) were completely or predominantly solid. In CEUS, 48.4% (15/31) of the tumors exhibited slow wash-in, while 77.4% (24/31) showed fast wash-out. Furthermore, 71.0% (22/31) demonstrated homogeneous peak enhancement, and 61.3% (19/31) displayed perilesional rim-like enhancement (PRE).ConclusionThe combination of conventional ultrasound features and CEUS characteristics of chRCC with quantitative echo intensity analysis enhances diagnostic objectivity and holds promise for non-invasive preoperative differentiation of RCC subtypes.